Persistent predator–prey dynamics revealed by mass extinction - Sallan, Lauren Cole (National Academy of Sciences, 2011)
Predator–prey interactions are thought by many researchers to define both modern ecosystems and past macroevolutionary events. In modern ecosystems, experimental removal or addition of taxa is often used to determine trophic relationships and predator identity. Both characteristics are notoriously difficult to infer in the fossil record, where evidence of predation is usually limited to damage from failed attacks, individual stomach contents, one-sided escalation, or modern analogs. As a result, the role of predation in macroevolution is often dismissed in favor of competition and abiotic factors. Here we show that the end-Devonian Hangenberg event (359 Mya) was a natural experiment in which vertebrate predators were both removed and added to an otherwise stable prey fauna, revealing specific and persistent trophic interactions. Despite apparently favorable environmental conditions, crinoids diversified only after removal of their vertebrate consumers, exhibiting predatory release on a geological time scale. In contrast, later Mississippian (359–318 Mya) camerate crinoids declined precipitously in the face of increasing predation pressure from new durophagous fishes. Camerate failure is linked to the retention of obsolete defenses or “legacy adaptations” that prevented coevolutionary escalation. Our results suggest that major crinoid evolutionary phenomena, including rapid diversification, faunal turnover, and species selection, might be linked to vertebrate predation. Thus, interactions observed in small ecosystems, such as Lotka-Volterra cycles and trophic cascades, could operate at geologic time scales and higher taxonomic ranks. Both trophic knock-on effects and retention of obsolete traits might be common in the aftermath of predator extinction.